Implementation Of Bureaucracy Simple Policy In Improving The Bureaucracy Reform Index The Government Of The City Of Salatiga - Priyono, Hari; Warsono, Hardi; Sunu Astuti, Retno (CV. Inara, 2022)
The targets of the Salatiga City Government Bureaucratic Reform are adjusted to the development targets of the state apparatus sub-sector, as stated in Presidential Regulation Number 18 of 2020 concerning the 2020-2024 National Medium-Term Development Plan (RPJMN), namely: a clean and accountable bureaucracy; capable bureaucracy; and excellent public service. This research uses the descriptive qualitative method. Qualitative research is research where the researcher is placed as a key instrument, the data collection technique is carried out by combining and analyzing the data and is inductive in nature. This research will use an inductive mindset, namely, the researcher goes into the field, studies a process of discovery which is a fact or event, and then records it. , analyze with a phenomenological approach then interpret and report and draw conclusions from the process.The result of his research was that the Mayor of Salatiga requested that the implementation of Bureaucratic Reform be followed up immediately. Digital signatures are expected to encourage effective and efficient bureaucratic processes. Public service problems include people's dissatisfaction with the time, cost, and method of service. The implementation of Bureaucratic Reform covers eight areas of change. In Salatiga, there are several assessment indices that have decreased in 2021.